POLITENESS STRATEGY BY ELLEN DEGENERES IN ELLEN SHOW WITH SENATOR HILLARY CLINTON AND THE PRESIDENT OF THE UNITED STATES MR. BARRACK OBAMA - Maria Skolastika; Yusniaty Galingging (Prodi Sastra Inggris UKI, 2019)
Politeness is used in many aspects of communication including mass media. This writing is focused on the pragmatic politeness of an interview on